Integrated Water Resources Management: A Study Of Public Willingness To Participate In Watershed Management Of Batu Kurau, Perak - Nazimuddin, Ridzwanurahim (2018)
Water resources management (WRM) is undergoing changes in Malaysia. There is now a shift towards the implementation of Integrated Water Resources Management (IWRM) in future Malaysian WRM planning. Part of this management paradigm is watershed management, where the watershed becomes the management unit upon which WRM is based. One aspect of watershed management (WM) is the inclusion of the public in decisionmaking processes, however this would depend upon the willingness to participate, (WTP) of the public in such processes. The objective of this study was to; 1) assess public WTP in watershed management and 2) assess factors that could influence public WTP in watershed management in respondents from three villages in Batu Kurau watershed. Batu Kurau was chosen as location of study due to the local population’s dependence on the watershed for their water resources. Thus, this context makes it interesting to evaluate the potential WTP of such respondents regarding involvement in WM of Batu Kurau. In order to answer the objectives, a questionnaire survey was developed consisting of constructs of factors determined from literature review; 1) socioeconomic factors, 2) knowledge of watershed issues, 3) values in water resources consumption, 4) satisfaction with water resources management, 5) satisfaction with watershed management, and 6) perception of involvement in watershed management. The scores of the respondents in WTP and also the above factors was analysed in descriptive analysis to answer the first objective. Chi-square cross-tabulation (for socioeconomic factors) and correlational analysis (for other factors) was used in order to answer the second objective. The survey was conducted in three villages in Batu Kurau, where 302 respondents (for 95% confidence level according to Krejcie & Morgan (1970)) were randomly sampled.